Transition-Metal-Catalyzed Arylation of 1-Deazapurines via C–H Bond Activation - Iaroshenko, Viktor O.; Ali, Iftikhar; Mkrtchyan, Satenik; Semeniuchenko, Volodymyr; Ostrovskyi, Dmytro; Langer, Peter (Synlett, 2012)
Transition-metal-catalyzed arylation of imidazo[4,5-b]pyridines (known as 1-deazapurines) is reported. 1-Deazapurines were synthesized from 5-aminoimidazoles, generated in situ by the reaction of methyl N-(cyanomethyl)formimidate with primary amines.
Keywords: catalysis; nickel; C–H activation; arylation; 1-deazapurine; imidazole